Polymorphism Analysis of VSX1 and SOD1 Genes in Greek Patients with Keratoconus. (3rd July 2015) - Moschos, Marilita M.; Kokolakis, Nikolaos; Gazouli, Maria; Chatziralli, Irini P.; Droutsas, Dimitrios; Anagnou, Nicholas P.; Ladas, Ioannis D.
Abstract: Background : A number of mutations in the VSX1 and SOD1 genes have been reported to be associated with keratoconus (KC), however the results from different studies are controversial. In this study, we conducted the genotyping of common polymorphisms [ VSX1 : D144E, H244R, R166W, G160D; SOD1 : intronic 7-base deletion (c.169 + 50delTAAACAG)], in a case–control sample panel of the Greek population. Materials and methods : A case–control panel, with 33 KC patients and 78 healthy controls, were surveyed. DNA from each individual was tested for the VSX1 : D144E, H244R, R166W, G160D and SOD1 : intronic 7-base deletion (c.169 + 50delTAAACAG) polymorphisms by direct sequencing. Results : We observed no polymorphisms of the VSX1 gene in the case–control panel. Concerning the SOD1 intronic 7-base deletion (c.169 + 50delTAAACAG), our findings suggest that heterozygous carriers are over-represented among KC cases compared to healthy controls ( p = 0.002). Conclusions : We cannot confirm the previously reported association of the polymorphism in the VSX1 gene with KC. Our results suggest a possible causative role of SOD 1 in the pathogenesis of KC. Further studies are required to identify other important genetic factors involved in the pathogenesis and progression of KC.